HIDUP SEHAT TANPA ROKOK BAGI SISWA SISWI SMP NEGERI 12 KONAWE SELATAN - Jabbar, Asriullah; Muliadi, Rahmat; Nasrudin, Nasrudin; Malik, Fadhliyah; Ningsih, Aprilia Surya; Andriyani, Elfi; Rahayu, Faulia Fajar; Amaliah, Nur Syafitri; Hasanah, Nur Uswatun; Mubarak, Mubarak; Y, Muhammad Ilyas (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Smoking represents a significant public health concern, with the potential to cause a range of diseases. Among adolescents, this phenomenon is on the rise, challenging long-held taboos surrounding its use. The objective of this service was to provide information and education to students of SMPN 12 Konawe Selatan. This activity was conducted using the lecture method and leaflet distribution. The results obtained from the 45 students who attended the counselling session demonstrated an increase in understanding, as evidenced by the pre- and post-test results.